2020
DOI: 10.1111/jfpp.14430
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soaking, steaming, and dehydration on the microstructure, physicochemical properties and in vitro starch digestibility of flour produced from Lablab purpureus (L.) Sweet (hyacinth bean)

Abstract: Hyacinth bean flour was produced from legume grains subjected to steaming and dehydration treatments, prior to soaking to improve utilization as potential functional food ingredients. The morphological characteristics of starch granules extensively changed in response to processing with a distinct variation in the chemical composition of samples studied. Potassium (215.33–326.33 mg/100 g), sodium (19.30–24.57 mg/100 g), and phosphorous (148.67–178.33 mg/100 g) were among the main contributors to total variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 43 publications
4
17
1
Order By: Relevance
“…51 The lower WSI of soaked-autoclaved flours may be attributed to the denaturation of proteins and the fact that before obtaining the flour, during the cooking of seeds, the soluble compounds of the broad beans could be leached out in the steam that condenses around them. 52,54 Results with the same tendency were reported by Naiker et al 49 and Simons and Hall. 52 Naiker et al 49 determined the WSI and SP of soaked and soaked-autoclaved hyacinth bean flours at different temperatures, and Simons and Hall 52 determined the WAI and WSI of raw and cooked pinto bean flours.…”
Section: Papersupporting
confidence: 85%
See 1 more Smart Citation
“…51 The lower WSI of soaked-autoclaved flours may be attributed to the denaturation of proteins and the fact that before obtaining the flour, during the cooking of seeds, the soluble compounds of the broad beans could be leached out in the steam that condenses around them. 52,54 Results with the same tendency were reported by Naiker et al 49 and Simons and Hall. 52 Naiker et al 49 determined the WSI and SP of soaked and soaked-autoclaved hyacinth bean flours at different temperatures, and Simons and Hall 52 determined the WAI and WSI of raw and cooked pinto bean flours.…”
Section: Papersupporting
confidence: 85%
“…25,48 Kumar et al 48 who measured the BD of soaked broad bean flour and pressure-cooked broad bean flour, obtained results with the same tendency but with lower values (0.58 and 0.71 g mL −1 , respectively). Naiker et al 49 also reported the same tendency but with hyacinth bean flour.…”
Section: Papermentioning
confidence: 58%
“…The low gelatinization and retrogradation properties shown in the DSC results of FT reflect in its low swelling power and high‐solubility results. The high swelling powers of the starches may also be related to the hydrophilic nature of hyacinth bean (Naiker et al ., 2020) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro starch digestibility was determined using the method described by Naiker et al . (2020) with minor modifications. In brief, 500 mg of the sample was stirred in 1 mL of porcine α‐amylase (Sigma 86250; 1.5 U mg −1 of carbonate buffer pH 7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation